Glycaemic control and hypoglycaemia benefits with insulin glargine 300 U/mL extend to people with type 2 diabetes and mild‐to‐moderate renal impairment. Issue 12 (30th August 2018) - Javier Escalada, F.; Halimi, Serge; Senior, Peter A.; Bonnemaire, Mireille; Cali, Anna M. G.; Melas‐Melt, Lydie; Karalliedde, Janaka; Ritzel, Robert A.
Abstract : Aim: To investigate the impact of renal function on the safety and efficacy of insulin glargine 300 U/mL (Gla‐300) and insulin glargine 100 U/mL (Gla‐100). Materials and Methods: A meta‐analysis was performed using pooled 6‐month data from the EDITION 1, 2 and 3 trials ( N = 2496). Eligible participants, aged ≥18 years with a diagnosis of type 2 diabetes (T2DM), were randomized to receive once‐daily evening injections of Gla‐300 or Gla‐100. Pooled results were assessed by two renal function subgroups: estimated glomerular filtration rate (eGFR) <60 and ≥60 mL/min/1.73 m 2 . Results: The decrease in glycated haemoglobin (HbA1c) after 6 months and the proportion of individuals with T2DM achieving HbA1c targets were similar in the Gla‐300 and Gla‐100 groups, for both renal function subgroups. There was a reduced risk of nocturnal (12:00‐5:59am ) confirmed (≤3.9 mmol/L [≤70 mg/dL]) or severe hypoglycaemia with Gla‐300 in both renal function subgroups (eGFR <60 mL/min/1.73 m 2 : relative risk [RR] 0.76 [95% confidence interval CI 0.62‐0.94] and eGFR ≥60 mL/min/1.73 m 2 : RR 0.75 [95% CI 0.67‐0.85]). For confirmed (≤70 mg/dL [≤3.9 mmol/L]) or severe hypoglycaemia at any time of day (24 hours) the hypoglycaemia risk was lower with Gla‐300 vs Gla‐100 in both the lower (RR 0.94 [95% CI 0.86‐1.03]) and higher (RR 0.90 [95% CI 0.85‐0.95]) eGFR subgroups. Conclusions: Gla‐300 provided similar glycaemic control to Gla‐100, while indicating a reduced overall risk of confirmed (≤3.9 and <3.0 mmol/L [≤70 and <54 mg/dL]) or severe hypoglycaemia, with no significant difference between renal function subgroups.